Assessing the reproducibility of an O‐glycopeptide enrichment method with a novel software, Pinnacle. Issue 24 (30th August 2018) - Pap, Adam; Prakash, Amol; F. Medzihradszky, Katalin; Darula, Zsuzsanna
Abstract: A novel software, Pinnacle was used to reassess the reproducibility of a 2‐step lectin‐based O ‐glycopeptide enrichment method. A publicly available dataset consisting of 12 data files representing 3 technical replicates of enriched glycopeptides from human serum was investigated. Previously, an attempt for reproducibility assessment was made utilizing an MS/MS scan (MS2)‐based method. However, the stochastic nature of precursor ion selection strongly biased this approach leading to underestimated rate of reproducibility. To bypass this problem, our present method follows the general path to confidently identify O ‐glycopeptides (database search with MS/MS data) supplemented with full scan/survey scan (MS1)/extracted ion chromatogram (XIC) mining in all files using two software packages, Pinnacle and Skyline. Confident MS/MS identifications were delivered by Protein Prospector. With this input Skyline indicated a 70% reproducibility for our workflow. However, Pinnacle performed better, indicating the presence of 90% of the confidently assigned glycopeptides in all the three replicates. Pinnacle, just like Skyline, performs ion extraction using the high accuracy, high resolution mass measurement data but it also utilizes all the available MS/MS spectra, even from different activation methods, within the same file to make mass spectrometric data evaluation for glycopeptides more reliable.